1977
DOI: 10.1146/annurev.me.28.020177.000345
|View full text |Cite
|
Sign up to set email alerts
|

IgA-Associated Glomerulonephritis

Abstract: In summary, IgA-associated glomerulonephritis is an interesting clinical problem. The immunohistochemical identification of renal IgA deposits is the sine qua non of its diagnosis, although most of the patients reported have had hematuric syndromes, particularly recurrent gross hematuria. The importance of this immunopathologic entity devolves from the crucial use of special stains to identify IgA, the enigmatic role of IgA, the usual mesangioapthic expression of histologic response, and the ill-defined relati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

1980
1980
2002
2002

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(2 citation statements)
references
References 8 publications
0
1
0
1
Order By: Relevance
“…2], Up to now the role of immune cells in this nephropathy has received little attention. This topic was not mentioned in the complete reviews on IgA nephropathy made by Lowance et al [3] and McPhaul [4], However, taking into account the high serum IgA levels found in these patients, the possible cel lular abnormalities ought to be suspected. In this regard, the existence of high serum levels of polymeric IgA [5], probably due to their elevated production by peripheral stimulation [6], has been demonstrated.…”
Section: Introductionmentioning
confidence: 99%
“…2], Up to now the role of immune cells in this nephropathy has received little attention. This topic was not mentioned in the complete reviews on IgA nephropathy made by Lowance et al [3] and McPhaul [4], However, taking into account the high serum IgA levels found in these patients, the possible cel lular abnormalities ought to be suspected. In this regard, the existence of high serum levels of polymeric IgA [5], probably due to their elevated production by peripheral stimulation [6], has been demonstrated.…”
Section: Introductionmentioning
confidence: 99%
“…Die Verschlechterung der Nierenfunktion hinkt der Hämaturie um durchschnittlich 4 Wochen hinterher. Die Nierenbeteiligung gleicht histologisch und im Verlauf einer IgA-Nephropathie Berger, der häufigsten Glomerulonephitis bei Erwachsenen in Asien und der westlichen Welt und vermutlich eine der Purpura Schönlein-Henoch verwandte Erkrankung (5,9,10). Dazu passt, dass sich ein Morbus Berger zu einer Purpura Schönlein-Henoch entwickeln kann (1,11,13).…”
Section: Diskussionunclassified